A comparative study of Norwegian and Swedish special educators' beliefs and practices. Issue 3 (26th May 2020) - Jortveit, Maryann; Tveit, Anne Dorthe; Cameron, David Lansing; Lindqvist, Gunilla
ABSTRACT: The purpose of this study was to examine and compare Norwegian (n = 320) and Swedish (n = 425) special educators' reported practices and beliefs about key aspects of their profession. Data was collected via surveys sent to graduates of special education programmes at four universities who completed their studies between 2001 and 2012. A sociological theory of professions and the dichotomous framework of relational and categorical perspectives was used to analyse survey responses. Despite many similarities, beliefs and reported practices in the two countries differed in a number of ways. Compared to Norway, traditional teaching activities (e.g. individual and small group instruction) appear to comprise a greater portion of special educators' work in Sweden. On the other hand, findings suggest that the relational perspective is more widespread in Sweden and the categorical perspective more dominant in Norway, although there are nuances to this pattern.